2002
DOI: 10.1093/jn/132.9.2551
|View full text |Cite
|
Sign up to set email alerts
|

Weaning Affects the Expression of Heat Shock Proteins in Different Regions of the Gastrointestinal Tract of Piglets

Abstract: Heat shock proteins (HSP) play a central role in the protection of cells, tissues or organs subjected to various types of stressors. Different nutrients have been recently shown to exert their protection through the induction of HSP. Because these nutrients alleviate alterations of the intestine after weaning in pigs, this study was designed to obtain basic information on the expression of HSP 27, heat shock cognate 70 (HSC 70), HSP 70 and HSP 90 along the gastrointestinal tract (GIT) of young pigs and to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 39 publications
6
34
0
3
Order By: Relevance
“…Furthermore, animal-to-animal variation and large interspecies variation have been found in Hsp70 expression in human, rat, and pig. This may be related to two functional promoter variants of hsp70 gene and the variation in stress susceptibility (David et al 2002;Khassaf et al 2001;Schwerin et al 2001). In the present study, we also observed that the hsp70 mRNA transcription varies with its corresponding Hsp70 protein expression in the same pattern.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Furthermore, animal-to-animal variation and large interspecies variation have been found in Hsp70 expression in human, rat, and pig. This may be related to two functional promoter variants of hsp70 gene and the variation in stress susceptibility (David et al 2002;Khassaf et al 2001;Schwerin et al 2001). In the present study, we also observed that the hsp70 mRNA transcription varies with its corresponding Hsp70 protein expression in the same pattern.…”
Section: Discussionsupporting
confidence: 77%
“…A similar variation has been found in the induction of Hsp70 in pig after transportation (Sepponen and Pösö 2006). In the gastrointestinal tract of pigs, weaning has been shown to cause abnormal spatial-temporal patterns of Hsp70 expression (David et al 2002). These imply that different intestinal sites had different responses to stress.…”
Section: Discussionsupporting
confidence: 64%
“…Recently, HSP 25 and HSP 70 were demonstrated to be implicated in the protective actions of butyrate [70] and glutamine [88], respectively, in cultured cells. Since these nutrients are known to alleviate small intestine PW alterations in piglets, we studied the impact of weaning on gut HSP patterns [16]. Most changes observed in HSP protein concentrations were precocious (6 to 48 h PW) and transient (Tab.…”
Section: Weaning and Intestinal Cell Protection By Heat Shock Proteinsmentioning
confidence: 99%
“…Weaning induced an early drop, followed by an Table IV. Post-weaning changes in the tissue levels of heat shock proteins (HSP) in various sites of the gut of young pigs weaned at 28 days of age (adapted from [16]). [20].…”
Section: Weaning and Intestinal Mucinsmentioning
confidence: 99%
“…Par ailleurs, Lallès, 2010). la plupart des HSP sont réduites dans l'iléon après sevrage, ce qui pourrait contribuer à expliquer les altérations de barrière à ce niveau (David et al 2002). Collectivement, les données disponibles confirment l'importance du stress, du système nerveux et des mastocytes dans l'apparition des troubles digestifs du sevrage chez le porcelet.…”
Section: Données Récentesunclassified